ACTIVE TEACHING-LEARNING SYSTEM AND CHALLENGES IN THE PROFESSIONAL EDUCATION - Palash Pal, Dilip Dey, Sourav Kumar Das, Debasish Maji, Banshidhari Samanta, Asit Kumar Mondal (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Now-a-days, the ways to develop professional educator have been changed. Students benefit more from teachers who are not only qualified and experienced but at the same time always have updated outcome base. Often need enrichment programmers to update the teachers and consequently to the students they teach. Even if a profession has people with the required qualifications and experience to stay in the job but no opportunities to improve, update knowledge base with changing time and growing needs, it affects their and also the students’ performance adversely. Based on this, only active teaching and learning system will give better development for upliftment of new comers.